Rediscovering Abdurrahman Wahid’s Ideas in Today’s Indonesia: the Use of Argumentative Devices in English Articles - Masduqi, Harits; Subiyanto, Arif; Chotib, Mochamad Nasrul (e-Journal of Linguistics; Vol 16 No 1 (2022): ejl-JanuaryDO - 10.24843/e-jl.2022.v16.i01.p02, 2021)
Recent issues on social and politics have become so influential in Indonesia that people are divided and become increasingly intolerant. In the era of intolerance it is quite right to rediscoverand analyse arguments of the late K.H. Abdurrahman Wahid, the fourth president of Indonesia that earned his reputation as an international religious scholar, a defender of pluralism, and a champion of humanity. This paper presents a discourse analysis on argumentative devices used byAbdurrahman Wahid in his English articles published at www.gusdur.net . Wahid used the eight argumentative devices masterfully in his articles. Evaluative expressive expressions were the most frequent argumentative device (31%). Wahid tended to show his value judgments bluntly, either positive or negative, to comment or react to current issues under discussion. Such an emotional tendency potentially came from Wahid’s own point of view that was based on things which were ideal for him, not on objective analyses made by other people.